Program Merdeka Belajar Kampus Merdeka Untuk Meningkatkan Micro-Skill Lulusan - Agus Arifin; Puput Puspitorini; Cecep Anwar H.F. Santosa; Yayat Ruhiat (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Merdeka Belajar—Free Campus (MBKM) is a major step towards transforming Indonesia's higher education system. MBKM adopts the idea of independent learning, provides curriculum flexibility, allows students to participate in learning outside the study program, and encourages close collaboration between universities, the business world and the world of work. So that MBKM becomes an effective forum for students to develop hard skills, soft skills and micro-skills. This research design uses a quantitative with correlational design to measure the relationship between variables. Population and Sample: 87 students in the Serang Regency, Tangerang Regency and Tangerang City, Banten Province, Indonesia. R-Square: The R-square value for Micro-Skills is 0.205 and for Curriculum Development is 0.217, indicating the moderate ability of the model in explaining data variability. Lower Adjusted R-square values (Micro-Skills: 0.166, Curriculum Development: 0.189) indicate model adjustment for the number of predictor variables. F-square: The effect size of the exogenous latent variable on the endogenous latent variable shows a significant contribution of Academic Culture to Curriculum Development (f-square: 0.221), while other relationships are less significant. Path Coefficient: A statistically significant relationship was only found between Academic Culture and Curriculum Development (P = 0.019). Other relationships, such as Social Culture and Ethnocentrism with Micro-Skills or Curriculum Development, did not show statistical significance. MBKM gives students the opportunity to improve social skills, self-management abilities, and the ability to adapt to the work environment. Graduates can develop micro-skills thanks to curriculum flexibility and collaboration with industry. Universities can improve MBKM by focusing on learning relevant to industry demands and field experiences such as internships or practical projects.